2001
DOI: 10.1073/pnas.181336098
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkey placental transgene expression after lentiviral gene transfer into preimplantation embryos

Abstract: Transgenic mice have provided invaluable information about gene function and regulation. However, because of marked differences between rodents and primates, some areas of human biology such as early embryonic development, aging, and maternal-fetal interactions would be best studied in a nonhuman primate model. Here, we report that gene transfer into rhesus monkey (Macaca mulatta) preimplantation embryos gives rise to transgenic placentas that express a reporter transgene (eGFP). Blastocysts resulting from cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 41 publications
(32 reference statements)
1
55
0
Order By: Relevance
“…Further analyses revealed that the transgene was present only in extraembryonic tissues such as the placenta (Wolfgang et al, 2001). By contrast, we observed efficient transduction of the embryo proper and extraembryonic cells after infection of bovine embryos and oocytes.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Further analyses revealed that the transgene was present only in extraembryonic tissues such as the placenta (Wolfgang et al, 2001). By contrast, we observed efficient transduction of the embryo proper and extraembryonic cells after infection of bovine embryos and oocytes.…”
Section: Discussionmentioning
confidence: 61%
“…The GFP transgene was not found in neonates developed from rhesus monkey embryos infected with lentiviral vectors (Wolfgang et al, 2001). Further analyses revealed that the transgene was present only in extraembryonic tissues such as the placenta (Wolfgang et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[31][32][33][34] These viruses have also been employed successfully to deliver exogenous genes to human cDC. [35][36][37][38] A major advantage of this vector system is its capacity to mediate stable foreign gene expression in non-dividing cells -a prerequisite for studies on DC activity.…”
Section: Discussionmentioning
confidence: 99%